Capital formation and agricultural growth in China - Ma, H.; Huang, J.; Oxley, Leslie (2013)
The paper considers the role and determinants of capital formation in Chinese agriculture and, in particular, the effects of capital formation on agricultural total factor productivity (TFP) growth. The results show that capital investment in agriculture by both government and farmers has risen significantly in the past two and a half decades, particularly in recent years. As China remains in the early stages of agricultural policy transition, its political economy would suggest that there will likely be more public investment in, and more subsidies to, agriculture in the coming years. Increased public investment in agriculture appears to have also induced increased farmers' capital formation in agriculture. Credit policy, the overall growth of farmer's income, rural wages, and comparative advantage of commodities are important factors that may facilitate farmers' investment in agriculture. The results also show that the successful growth of China's agriculture has been associated with its high TFP growth. Both public and private agricultural capital formations have played an important role in raising China's agricultural productivity. The TFP decomposition analyses show that technological change is a primary driver of the TFP growth in China's agriculture. © 2013 The Earth Institute at Columbia University and the Massachusetts Institute of Technology.